Interobserver variability in diagnosing thyroid fine-needle aspiration cytology using the 2023 Bethesda system for reporting thyroid cytopathology - Pratima Manohar Pattar; Sameera N Patel; Girija (Asian Journal of Medical Sciences, 2025)
Background: Thyroid fine-needle aspiration (FNA) surfaced as a vital first-line diagnostic tool to categorize them into benign or malignant, thereby reducing unnecessary surgeries in benign nodules. The Bethesda system for reporting thyroid cytopathology (TBSRTC) has established a standardized, category-based reporting system and since then it has been widely adopted by cytopathologists in worldwide. It has been shown that thyroid pathology contributes significantly to second-opinion discrepancies for cytopathology specimens. Aims and Objectives: To establish the reproducibility of TBSRTC in diagnosing thyroid lesions. To determine the interobserver variation in thyroid cytopathology using the 2023 TBSRTC. Materials and Methods: This was a 2-year retrospective study conducted in the Department of Pathology, from January 2018 to December 2019. Previous archived slides of thyroid FNA cytology were examined by three trained pathologists in a double-blinded fashion and were reclassified according to the 2023 TBSRTC. The results were evaluated for interobserver variability using Cohen’s kappa statistics and Statistical Package for the Social Sciences software version 24.0. Results: The present study included a total of 156 patients with a female: male ratio of 3: 0.1 and the mean age of 37.8±2.4 years. The interobserver agreement, calculated using Kappa statistics, for observer 1 and observer 2 was 0.735; for observer 1 and 3 was 0.841; and for observer 2 and 3 was 0.838. These values together showed substantial interobserver agreement. Conclusion: The 2023 TBSRTC gives a distinctive, universal, and homogeneous terminology for reporting the thyroid cytology and its execution should be promoted due to its virtual ease of reproducibility.